Pemertahanan Nilai Budaya Suku Dayak Maanyan Melalui Narasi Fabel di Daerah Aliran Sungai Barito - Nirena Ade Christy; Ibnu Yustiya Ramadhan; Ade Yusuf Ferudyn; Stefani Ratu Lestariningtyas; Sartika Dewi; Christian J Siallagan (FKIP, Universitas Palangka Raya, 2024)
The Dayak Maanyan culture has traditional values that can be seen in the Popular Fables of the Dayak Maanyan Tribe. These values are introduced from generation to generation, so that the values in the Dayak Maanyan tribe are not destroyed. The childhood of the Dayak Maanyan tribe is built through the storytelling of the Popular Fables of the Dayak Maanyan Tribe. Parents in the Dayak Maanyan tribe are important agents in educating their children regarding the values of the Dayak Maanyan tribe that can be conveyed through the Popular Fables of the Dayak Maanyan Tribe. This study will examine the intrinsic and extrinsic elements contained in the Popular Fables of the Dayak Maanyan Tribe. The intrinsic values that will be studied are the cultural values and cultural identity of the Dayak Maanyan tribe in the Popular Fables of the Dayak Maanyan Tribe. While the extrinsic values that will be studied are efforts to maintain cultural values and increase understanding and appreciation of the culture of the Dayak Maanyan tribe in the popular fable book of the Dayak Maanyan Tribe. The method used is qualitative descriptive, where all data is qualitative data that is studied and analyzed in the form of descriptions. The expected results are to provide understanding, show roles, identify strategies and preservation efforts, and provide recommendations related to the popular Dayak Maanyan fable book.